Enhanced effects of maghemite nanoparticles on the flocculent sludge wasted from a high-rate anammox reactor: Performance, microbial community and sludge characteristics. (February 2018) - Zhang, Zheng-Zhe; Cheng, Ya-Fei; Bai, Yu-Hui; Xu, Lian-Zeng-Ji; Xu, Jia-Jia; Shi, Zhi-Jian; Zhang, Qian-Qian; Jin, Ren-Cun
Highlights: The impact of MHNPs on anammox biomass was investigated for the first time. MHNPs at 1–200 mg L −1 did not show short-term toxicity to anammox biomass. MHNPs at 1–200 mg L −1 had no adverse effects on reactor performance. The addition of MHNPs increased the relative abundance of Ca. Kuenenia . SAA and EPS content were increased with elevated MHNP concentrations. Abstract: Magnetic nanoparticles (NPs) have been widely applied in environmental remediation, biomass immobilization and wastewater treatment, but their potential impact on anaerobic ammonium oxidation (anammox) biomass remains unknown. In this study, the short-term and long-term impacts of maghemite NPs (MHNPs) on the flocculent sludge wasted from a high-rate anammox reactor were investigated. Batch assays showed that the presence of MHNPs up to 200 mg L −1 did not affect anammox activity, reactive oxygen species production, or cell membrane integrity. Moreover, long-term addition of 1–200 mg L −1 MHNPs had no adverse effects on reactor performance. Notably, the specific anammox activity, the abundance of hydrazine synthase structural genes and the content of extracellular polymeric substance were increased with elevated MHNP concentrations. Meanwhile, the community structure was shifted to higher abundance of Candidatus Kuenenia indicated by high-throughput sequencing. Therefore, MHNPs could be applied to enhance anammox flocculent sludge due to their favorable biocompatibility.